Layer-by-Layer Oxidation for Decreasing the Size of Detonation Nanodiamond - Etzold, Bastian; Neitzel, Ioannis; Kett, Manfred; Strobl, Florian; Mochalin, Vadym N.; Gogotsi, Yury (Chemistry of Materials, 2014)
Diamond nanoparticles attract much attention as they combine outstanding mechanical properties with biocompatibility and are available in large quantities. Control and tunability of the particle size is very important for any nanomaterial. Although oxidation can burn carbon and lead to a particle size decrease, this technique could not be successfully employed for nanodiamond size reduction on the nanoscale. In this work, two commercial nanodiamond powders are used to demonstrate separation of the oxidation reaction into two steps (i) the oxygen chemisorption and (ii) the CO and/or CO2 desorption. This allows for an effective control of the oxidation process. In situ thermogravimetric analysis suggests that the oxidation is thermodynamically rather than kinetically controlled, and that the carbon burn off can be adjusted by repeating chemisorption/desorption steps to remove carbon layer after layer. Small-angle X-ray scattering (SAXS) characterization of the diamond nanoparticles showed a continuous size decrease from 5.2 to 4.8 nm during 15 layer-by-layer (LbL) oxidation cycles, in contrast to average particle size increase observed in the case of continuous oxidation in air. In accordance with the size decrease after LbL oxidation, the specific surface area (SSA) of the nanopowders increased.
EAM Import::2019-03-12

Recommendations for the Production of Silicon Carbide-derived Carbon Based on Intrinsic Kinetic Data - Knorr, Tilman; Strobl, Florian; Glenk, Friedrich; Etzold, Bastian (Chemical Engineering & Technology, 2012)
Recommendations for mode of operation and critical dimensions regarding inner mass transfer limitation were deduced for the technical extraction of silicon from silicon carbide to produce nanoporous carbon (carbide-derived carbon, CDC). The recommendations are based on intrinsic kinetics derived from experimental data and reaction engineering simulation of the transient process (shrinking-core like mechanism). As the reaction takes place at 1000 °C under chlorine atmosphere, kinetic data as well as diffusion coefficients are extracted from integral conversion data in a lab scale reactor. The reaction rate dependency for varying chlorine concentrations is represented best by a Hougen-Watson type rate approach with dissociative adsorption of a reactant. From the experimental data the effective diffusion coefficient of chlorine in the resulting nanoporous carbon could also be derived to 4 · 10–8 m2s–1 at 1000 °C.
EAM Import::2019-03-13